Geographically conserved microbiomes of four temperate water tunicates. Issue 4 (28th April 2016) - Cahill, Patrick L.; Fidler, Andrew E.; Hopkins, Grant A.; Wood, Susanna A.
Summary: Tunicates are useful models for exploring microbiomes because they have an innate immune system resembling that of chordates. Automated ribosomal RNA intergenic spacer analysis and High‐Throughput Sequencing were used to compare the tunic microbiomes of Ciona robusta (formerly Ciona intestinalis type A), Ciona savignyi, Botrylloides leachi and Botryllus schlosseri sampled from three distinct locations with limited genetic connectivity. Bacterial phylotype profiles were conserved within each species, and there were no detectable differences between tunic and tunic + cuticle subsamples from an individual. Bacterial operational taxonomic unit (OTU) diversity was lowest for C. savignyi (320 ± 190 OTUs) and highest for B. schlosseri (1260 ± 190 OTUs). Each species had a distinct set of bacterial OTUs (pseudo‐F = 3.0, p  > 0.001), with the exception of B. leachi and B. schlosseri from one sampling location ( t  = 1.2, p  = 0.09). Of note were OTUs assigned to Alphaproteobacteria from C. robusta plus Phyllobacteriaceae and Endozoicomonas from C. savignyi . These OTUs contributed 51, 22 and 10% of sequence reads, respectively, and are related to known bacterial symbionts. The within‐species conservation of core OTUs across three distinct and co‐occurring populations of tunicates provides compelling evidence that these tunicates foster defined microbiomes.